Risk factors at five-year survival in grade 3 breast cancer: a retrospective observational study of the New Zealand population - Sharita Meharry; Robert Borotkanics; Reena Ramsaroop; Fabrice Merien (BMC, 2021)
Abstract Background Breast cancer is the most common cancer in New Zealand, with approximately 3000 new registrations annually, affecting one in nine women and resulting in more than 600 deaths. This study analyzed data of patients with selected prognostic factors of Nottingham grade 3 tumors over a specified five-year period. The study aimed to identify factors that result in differential survival in the female, New Zealand population. Method This is an observational, retrospective cohort study of prospectively collected data from New Zealand Breast Cancer Register. The selected period of 1st January 2011 to 31st, December 2015 allowed a consistent overlap for a national five-year data of grade 3 breast cancer in New Zealand. Mortality was carried out using univariate Fine-Gray competing risk statistical models. Results This study showed that women in the older age group (> 70 years) had higher five-year mortality risk (HR: 1.7, 95% CI: 0.9-3.0, p = 0.053). Hormonal receptor analysis showed that ER positive, PR negative, and ER negative, PR negative subjects were at increased risk (HR = 3.5, 95% CI 2.3-5.4, p < 0.001) and (HR = 2.6, 95% CI, 1.8-3.9, p < 0.001) respectively. Molecular subtypes Triple Negative Breast Cancer and Luminal B subjects were at increased risk (HR = 3.0, 95% CI, 1.8-4.7, p < 0.001 and (HR = 3.3, 95% CI, 1.7-6.3, p < 0.001) respectively. HER2 enriched subjects were at a higher, but not significant, risk of five-year mortality compared to luminal A (HR = 1.6, 95% CI, 0.8-3.0, p = 0.10). NZ Europeans were at increased risk (HR = 1.7, 95% CI, 0.8-3.2, p = 0.11), with the highest Cumulative Incidence Function CIF, the largest proportion of HER2 enriched and TNBC across ethnicities.; however, Pacific Islanders experienced the highest HER2 CIF. Conclusion The survival rates for grade 3 breast cancer vary across the selected prognostic factors and ethnicity. The results of this study make an initial contribution to the understanding of grade 3 breast cancer in the New Zealand population.